FROM DISTRESS TO DISCLOSURE: UNDERSTANDING THE MODERATING ROLE OF LEVERAGE IN ACCOUNTING CONSERVATISM UNDER INFORMATION ASYMMETRY - Edi Triwibowo; Dian Sulistyorini Wulandari; Cecilia Margaretha Sinaga (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the effect of financial distress and information asymmetry on accounting conservatism, with leverage as a moderating variable. The study uses panel data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. The research method adopts a quantitative explanatory approach, employing purposive sampling and panel data regression analysis using multiple linear regression and moderated regression analysis (MRA). The findings show that both financial distress and information asymmetry have a significant positive effect on accounting conservatism. However, leverage has a significant negative effect on conservatism, indicating that highly leveraged firms are less conservative in their reporting. Furthermore, the interaction between financial distress and leverage does not have a significant moderating effect, while leverage significantly moderates the relationship between information asymmetry and accounting conservatism. These results highlight the strategic role of conservative accounting in conditions of financial pressure and asymmetric information, especially when combined with high leverage. The study contributes to the literature on financial reporting by offering insights into how internal risk conditions and capital structure shape accounting policy decisions in emerging markets like Indonesia.